Pituitary Tumors A Clinical Casebook (Springer International Publishing, 2018)
Comprised of cases presenting diverse clinical scenarios involving pituitary tumors and related conditions, this concise, practical casebook provides clinical endocrinologists with the best real-world strategies to properly diagnose and treat the various presentations and symptoms they may encounter in daily practice. Discussing macroprolactinoma, non-functioning adenoma, TSH-secreting adenoma, Cushing's disease and acromegaly, each chapter is a case that provides a unique clinical presentation of a patient's symptoms and clinical findings, diagnostic work-up and the thought process involved in navigating the treatment options, as well as the supporting evidence. Cases included illustrate different types of tumors, related disorders and special situations and considerations, in addition to various management strategies, complications and outcomes, with helpful clinical pearls and pitfalls. Pragmatic and reader-friendly, Pituitary Tumors: A Clinical Casebook is written by experts in the field and is designed to facilitate and guide endocrinologists in the sometimes challenging decision-making process by presenting real case scenarios that span the spectrum of pituitary tumor presentations and treatment options.